The Inhibitory Effect of Lactobacillus plantarum and Some Spices in Growth of E. coli O157:H7 in Minced Beef - Salman, J. A. S.; Khalil, G. M.; Abdul-Razaq, R. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Inhibitory effect  of  Lactobacillus plantarum was studied against Escherichia coli O157:H7 in  minced  beef , as well as the effect of some Spices ( Garlic , Cloves and Black Pepper ) was studied against this bacteria . Plate count method was used to estimate the viable cells of  E. coli O157:H7 in the treated meat samples for incubation periods( 0 , 24  and 48) h.   Results showed  that  Lactobacillus plantarum had inhibitory effect  against  E. coli O157:H7 , when reducing the number of cells after 24, 48 h., and reached to Zero after (24) h. As well as Spices in this study had inhibitory activity against  E. coli O157:H7 .Garlic had the highest inhibitory effect  compared with Cloves and Black Pepper.    The synergistic inhibitory effect  of the combination of Lactobacillus plantarum and Spices ( Garlic , Cloves and Black Pepper ) separately were studied against  E. coli O157:H7 in the   minced  beef using the same method of counting .      Results showed  that the combination of  Lactobacillus plantarum  and spices   had a synergistic inhibitory effect  against  E. coli O157:H7. The synergistic Inhibitory effect  of Lactobacillus plantarum  and garlic in (24)h. incubation period was higher than the effect of other spices.